Challenges and Opportunities in Integrating ICT into Teaching and Learning: A Study of Higher Educational Institutions in Iraqi Kurdistan - Awrahman, Banan Jamil; Aziz, Chya Fatah; Said, Karzan Wakil (Universitas Negeri Semarang, 2023)
The integration of ICT has transformed conventional teaching methods in universities; however, obstacles such as the digital divide hinder its usage. This study employs a survey method to examine the challenges of incorporating ICT into teaching and learning in higher educational institutions in the Kurdistan Region of Iraq. Teachers from various universities across Kurdistan participated in a survey divided into three segments: the impact of ICT on students, difficulties in using ICT tools in teaching, and positive experiences of educators using ICT. The study utilizes machine learning modules to identify relationships between the challenges and ICT tools. The results demonstrate that the use of ICT tools has a positive impact on students, but challenges such as a lack of facilities and training hinder their use. Ultimately, the study concludes that integrating ICT into teaching and learning in higher educational institutions in Iraqi Kurdistan is vital, and emphasizes the need for additional training and resources to support the process. Abstrak Integrasi TIK telah mengubah metode pengajaran konvensional di perguruan tinggi; namun, hambatan seperti kesenjangan digital menghambat penggunaannya. Penelitian ini menggunakan metode survei untuk mengkaji tantangan pengintegrasian TIK dalam pengajaran dan pembelajaran di lembaga pendidikan tinggi di Wilayah Kurdistan, Irak. Guru-guru dari berbagai perguruan tinggi di Kurdistan berpartisipasi dalam survei yang terbagi menjadi tiga segmen: dampak TIK pada mahasiswa, kesulitan penggunaan alat TIK dalam pengajaran, dan pengalaman positif pendidik dalam menggunakan TIK. Penelitian ini menggunakan modul pembelajaran mesin untuk mengidentifikasi hubungan antara tantangan dan alat TIK. Hasil penelitian menunjukkan bahwa penggunaan alat TIK memiliki dampak positif pada mahasiswa, tetapi tantangan seperti kurangnya fasilitas dan pelatihan menghambat penggunaannya. Pada akhirnya, penelitian ini menyimpulkan bahwa integrasi TIK dalam pengajaran dan pembelajaran di lembaga pendidikan tinggi di Kurdistan Irak sangat penting, dan menekankan perlunya pelatihan dan sumber daya tambahan untuk mendukung proses tersebut.